Penilaian Autentik pada Mata Pelajaran Fikih di Madrasah Ibtidaiyah Nurul Falah Kerta - Muhammad Al Amin; Ina Aulia; Neneng Aisyah; Saefudin Zuhri; Wahyu Hidayat (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Authentic assessment is an assessment that becomes an important component to measure the success and progress of students in elementary school. However, so far the assessment has not comprehensively measured all the objectives in learning and not all domains can be measured in the assessment process. The purpose of this study was to find out how the implementation of authentic assessment in fiqh subjects at MI Nurul Falah Kerta. The formulation of the problem in this study is how to carry out an authentic assessment of fiqh subjects at MI Nurul Falah Kerta. This type of research is field research and the approach uses a qualitative approach. the informant of this study was a teacher of fiqh at MI Nurul Falah Kerta. Data collection techniques used in this research are interview, observation, and documentation techniques. The data processing techniques presented are in the form of descriptions, so that the problems can be described in full. From the results of this study, the assessment carried out by the teacher was in accordance with the existing standards in the authentic assessment of the 2013 curriculum.